Context Facilitates Performance on a Classic Cross-Cultural Emotion Perception Task - Hoemann, Katie (Emotion, 2018)
The majority of studies designed to assess cross-cultural emotion perception use a choice-from-array task in which participants are presented with brief emotion stories and asked to choose between target and foil cues. This task has been widely criticized, evoking a lively and prolonged debate about whether it inadvertently helps participants to perform better than they otherwise would, resulting in the appearance of universality. In three studies, we provide a strong test of the hypothesis that the classic choice-from-array task constitutes a potent source of context that shapes performance. Participants from a remote small-scale (the Hadza hunter-gatherers of Tanzania) and two urban industrialized (China and the United States) cultural samples selected target vocalizations that were contrived for six non-English, non-universal emotion categories at levels significantly above chance. In studies of anger, sadness, fear, disgust, happiness, and surprise, above chance performance is interpreted as evidence of universality. These studies support the hypothesis that choice-from-array tasks encourage evidence for cross-cultural emotion perception. We discuss these findings with reference to the history of cross-cultural emotion perception studies, and suggest several processes that may, together, give rise to the appearance of universal emotions.